Structures that support multi-functionality in interior spaces )apartments with limited space) (Al-Academy, 2024)
Reaching the basic foundations of the research topic (structures that support multi-functionality in interior spaces (apartments with limited space as a model)) the research problem was defined according to the following question: How to activate structures for interior spaces with limited space?The research objective was defined as follows: The research aims to reveal the extent of the possibility of employing structures in limited interior spaces. The research was also defined by three limits and the terms related to the subject of the research were defined (structures, multi-functionality, and interior space). The second chapter included two sections, the first (structures and function), and the second (residential interior spaces and the multi-functionality therein). The theoretical framework was also combined with a set of indicators that helped the researcher create an analysis form.